Anesthesia for Emergency Cesarean Section - Haque, MF; Sen, S; Meftahuzzaman, SM; Haque, MM (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):221-6.The abstract of this article is available on the PubMed website